Mechanistic aspects of wet and dry CO oxidation on Co3O4 nanorod surfaces: a NAP-UPS study - Ruchi Jain; Gnanakumar, Edwin S.; Gopinath, Chinnakonda S. (ACS Omega, 2017)
Catalytic activity, electronic structure, and the mechanistic aspects of Co3O4 nanorod (NR) surfaces have been explored for CO oxidation in dry and wet atmosphere using near-ambient pressure ultraviolet photoelectron spectroscopy. Presence of water with CO + O2 plummets the catalytic activity because of the change in the electronic nature from predominantly oxide (without water in feed) to a Co3O4 surface covered by a few intermediates. However, at ≥375 K, the Co3O4 surface recovers and regains the oxidation activity, at least partially, even in the presence of water. This is fully supported by the changes observed in the work function of Co3O4 under wet (H2O + CO + O2) conditions compared with dry (CO + O2) conditions. This study focuses on the comparative CO oxidation rate on Co3O4 NR surfaces and highlights the changes in the electronic structure that occur in the catalyst during the CO oxidation reaction.
Keywords: Catalyst; Nano Structures; Power X-Ray Diffraction; spectra; Water Vapor